3x-2y=6-4y

Simple and best practice solution for 3x-2y=6-4y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-2y=6-4y equation:


Simplifying
3x + -2y = 6 + -4y

Solving
3x + -2y = 6 + -4y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2y' to each side of the equation.
3x + -2y + 2y = 6 + -4y + 2y

Combine like terms: -2y + 2y = 0
3x + 0 = 6 + -4y + 2y
3x = 6 + -4y + 2y

Combine like terms: -4y + 2y = -2y
3x = 6 + -2y

Divide each side by '3'.
x = 2 + -0.6666666667y

Simplifying
x = 2 + -0.6666666667y

See similar equations:

| 20+x+x+5=45 | | 88-(6x+5)=6(x+3)+x | | 9-5n=15-2n | | p=3n+3w | | 20x+x=0 | | 32-2n=0 | | 12x+4=10x+10 | | 4a+11=a+11 | | 0.4p+3=0.2(p+5)+0.2(p+1) | | 5d-3=7d+9 | | 2x+4x+16=0 | | 2b+9=5b+15 | | 0.7w=14 | | 9x-8(x+5)=6-3x | | 17x+45=8x+10 | | 5x+18= | | 3x-4=-22-3x | | ax+dy-3c=c | | 10+2(7x-3)=5x-4 | | 8-2(3-2x)=3(x-1) | | 5t-3t=5-3(t+5) | | 4-4x=36 | | 0.2x^2=0.4x+2 | | 7x-2x=100 | | 13x^2+3x+2=0 | | 2x-x=50 | | -4(x+5)+2=6(x+6)-15 | | (x-5)(x-12)= | | 3x+15=3x+15 | | T=8ny | | 7b-6=18-5b | | -4x+3= |

Equations solver categories